Relationship between Employer Branding, CSR and Social Media Communication - Bašić, Ilarija; Ćorić, Nino; Brkić, Nenad (Naše gospodarstvo/Our economy, 2025)
This research aims to examine whether employer branding (EB) activities are related to the ranking of the Most Desirable Employer in Bosnia and Herzegovina (BiH), and to explore the correlation between EB, corporate social responsibility (CSR), and organisational representation on social media. The research was conducted among employees of 15 organisations ranked as the Most Desirable Employers, potential employees, and final-year university students from various academic fields. While in developed countries, specialised companies focus on talent attraction and recruitment as part of EB strategies, employers in BiH have yet to reach that level of long-term workforce planning and fully recognise the strategic benefits EB can offer. The findings indicate that EB significantly influences employer’s desirability among current and potential employees, and that organisations perceived as socially responsible tend to enjoy a stronger employer brand and are considered more desirable. Moreover, the analysis revealed no significant differences in the perception of the relationship between socially responsible business practices and organisational representation on social media between current and potential employees. The study’s key contributions include the finding that EB correlates positively with employer desirability; and that the impact of perceived dimensions of EB attractiveness is evident from the perspectives of both current and potential employees.
Keywords: Employer Branding; Corporate Social Responsibility; Social Media Communication; Most Desirable Employer